Proyecto de valoración de la marca “arcor”, aplicando los métodos de valoración de interbrand, modelo de damoran corregido por fernández y método de houlinan valuation. - Criollo Páez, Carlos Roberto (2011)
The value of assets is a subject of study to finances, investments valuation, enterprises, assessment, aggregate value tax and value management, the creation of value is object of study to some specialist at a world level, currently we can describe to Asvath Damoran, Pablo Fernandez, Fernando Rojo-Ramirez. Inside the management and creation of value we can obviate the contribution to the creation of enterprises value related with the intangible assets, in special to the mark. So it is as the marketing and finances converge in branding, which is a discipline to study the creation, strategy and marks management, when it is studied the mark contribution to the value creation, it is unquestionable that mark is converted in one asset so that it generates a value. In Ecuador, as in some countries of Latin America, the value of mark is something unquestionable, however the formal determination or scientifically based of the value to this kind of assets is few or nothing known. Due this reason it shall be applied three valuation methods ( Interband, Damoran corrected by Fernandez and Houlinan Valuation Advisors) and we shall analyze its result in Ecuador.